2018
DOI: 10.5070/bp330137614
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dangerous Disconnect Between Perspectives, Planning, Policy, and Practice Towards Informal Traders in Durban, South Africa

Abstract: While cities pursue recognition on the global scale, low-income populations are often negatively impacted by urban growth. Informal workers in Durban, South Africa have fallen victim to this trend, as the municipality's focus shifts to drawing international investment and cleaning up the city. In this article, I explore the question: How do municipal employee perspectives, current planning and policy documents, and current practice in the city align regarding treatment of informal traders in Durban, South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Since the mid-1990s, downtown Durban has experienced a visible infl ux of migrant street traders and the growth of informality (Devries 2018;Moyo and Gumbo 2021); in response, the city has aimed to address inequality and create a "liveable" and a "sustainable" city for the future (Sutherland et al 2018). Research by Ndumiso Sidzatane and Pranitha Maharaj (2013) almost a decade ago on street trading at Durban's Workshop Market, the site of the research in this article, found that, despite a few incidents where local traders referred to migrant traders as criminals who reduce the prices on goods, such lamentations did not incite violence or hostility within the market.…”
Section: Migration and Informal Street Trading At Durban's Workhop Ma...mentioning
confidence: 99%
“…Since the mid-1990s, downtown Durban has experienced a visible infl ux of migrant street traders and the growth of informality (Devries 2018;Moyo and Gumbo 2021); in response, the city has aimed to address inequality and create a "liveable" and a "sustainable" city for the future (Sutherland et al 2018). Research by Ndumiso Sidzatane and Pranitha Maharaj (2013) almost a decade ago on street trading at Durban's Workshop Market, the site of the research in this article, found that, despite a few incidents where local traders referred to migrant traders as criminals who reduce the prices on goods, such lamentations did not incite violence or hostility within the market.…”
Section: Migration and Informal Street Trading At Durban's Workhop Ma...mentioning
confidence: 99%